Cutting Sugar Cane, Trinidad - (:unkn) unknown (Davidson and Todd, Ltd., 2009)
A picture of labourers in the cane field cutting and loading the crop onto carts, the sugar factory buildings can be seen in the background.
Colour: Sepia; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Sugarcane industry--Trinidad and Tobago; Sugarcane--Trinidad and Tobago; Working class--Trinidad and Tobago; Carriages and carts--Trinidad and Tobago; Sugar factories--Trinidad and Tobago